2018
DOI: 10.1111/jdv.14950
|View full text |Cite
|
Sign up to set email alerts
|

The role of phototherapy in the surgical treatment of vitiligo: a systematic review

Abstract: Vitiligo is frequently treated with the combination of phototherapy and melanocyte transplantation. However, the additional benefit of phototherapy is unclear. Moreover, the optimal type and regimen of phototherapy are unknown. The objective of this systematic review was to identify whether phototherapy improves the outcome of melanocyte transplantation in vitiligo. We searched and screened for eligible studies in the databases of MEDLINE, EMBASE and CENTRAL. We included all clinical studies investigating mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…50%, 75% or 90% repigmentation). Studies that provided a form of additional treatment (such as NB‐UVB, PUVASOL, excimer laser) were excluded from the pooled analysis since these could influence the outcomes 18 . Tables 2a, b and c show the number of lesions reaching >50%, >75% and >90% repigmentation, respectively, after NCST per DR expansion ratio used.…”
Section: Resultsmentioning
confidence: 99%
“…50%, 75% or 90% repigmentation). Studies that provided a form of additional treatment (such as NB‐UVB, PUVASOL, excimer laser) were excluded from the pooled analysis since these could influence the outcomes 18 . Tables 2a, b and c show the number of lesions reaching >50%, >75% and >90% repigmentation, respectively, after NCST per DR expansion ratio used.…”
Section: Resultsmentioning
confidence: 99%
“…Phototherapy has been the principal treatment for vitiligo for decades and includes psoralen and ultraviolet A (PUVA) and NBUVB phototherapy. 6,16 Although PUVA is an effective therapy, it has several limitations, including phototoxic effects, nausea and a potential risk of skin cancer. On the contrary, NBUVB phototherapy has gradually taken the place of PUVA phototherapy due to the lack of a photosensitizer, lower cumulative dose and fewer adverse effects, and is now considered the standard therapy for generalized vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Although PUVA is an effective therapy, it has several limitations, including phototoxic effects, nausea and a potential risk of skin cancer. On the contrary, NBUVB phototherapy has gradually taken the place of PUVA phototherapy due to the lack of a photosensitizer, lower cumulative dose and fewer adverse effects, and is now considered the standard therapy for generalized vitiligo 6,16 . NBUVB phototherapy was reported to be highly effective in restoring pigmentation in patients affected by vitiligo, showing no side‐effects, 17 and a recent meta‐analysis confirmed that a long duration of phototherapy should be encouraged to enhance the treatment response in vitiligo, mainly for the face and neck where a greater response is commonly observed 16…”
Section: Discussionmentioning
confidence: 99%
“…Other unwanted UV effects include sunburn, immunosuppression, eye damage and skin ageing [2]. On the other hand, there are many known positive effects and uses of UV light, including its therapeutic effects (e.g., in treating infants suffering from jaundice [3]; in treating skin, sleep, mood and seasonal affective disorders [4]; in treating vitamin D deficiency [5]; wound healing [6]) and further applications in medicine, such as its use in air ventilation systems in hospitals, in air/water purification, in disinfection in surgery, and much more [7,8].…”
Section: Introductionmentioning
confidence: 99%